Pengaruh Kegiatan Kerohanian Islam (Rohis) terhadap Prestasi Belajar Aqidah Akhlak Siswa Kelas IX MTs. Swasta Al-Ikhlas Pangkalan Susu - Indra Syah Putra; Ully Rachmaini Sitanggang (Fakultas Syariah IAIN Laa Roiba Bogor, 2020)
The formulation of the problem in this study are: (1) How are Islamic spiritual activities for grade IX students of MTs. Private Al-Ikhlas Pangkalan Susu?, (2) How is the learning achievement of Aqidah Akhlak students of class IX MTs. Private Al-Ikhlas Pangkalan Susu?, (3) How is the influence of Islamic spiritual activities on learning achievement of Aqidah Akhlak students of class IX MTs. Private Al-Ikhlas Dairy Base? The type of research used in this study is a quantitative research method. This research is categorized into a quasi-experimental research (quasi-experimental). The design used in this study includes three stages, namely: (1) The stage of preparation of learning tools and research instruments, (2) The stage of testing learning tools and research instruments, (3) The stage of implementing the experiment. Each stage is designed so that valid data is obtained according to the characteristics of the variables in accordance with the research objectives. Data collection techniques, namely using non-test. The instruments used in this study were observation guidelines, interview guidelines, questionnaire guidelines, and documentation guidelines. Questionnaires given to respondents were processed by tabulation, namely in the form of tables, for hypothesis testing, the Product Moment correlation formula will be used (Arikunto, 2014). Furthermore, the requirements test and data analysis were carried out to determine the extent of the effect. The results showed that: 1. Islamic spirituality activities (ROHIS) in grade IX students of Madrasah Tsanawiyah Swasta Al-Ikhlas Pangkalan Susu were very good (64%); 2. Student achievement for grade IX students of Madrasah Tsanawiyah Private Al-Ikhlas Pangkalan Susu is very good (57 %);3. The influence of Islamic spiritual activities (ROHIS) contributes positively and convincingly to the learning achievement of Aqidah Akhlak students of class IX MTs. Private Al-Ikhlas Pangkalan Susu with a moderate or moderate level of significance. So it can be concluded that there is a positive and significant relationship between Islamic spiritual activities (ROHIS) and the learning achievement of the moral aqidah students of class IX Madrasah Tsanawiyah Swasta Al-Ikhlas Pangkalan Susu.